A Proposal to Increase Value and Equity in the Development and Distribution of New Pharmaceuticals. (July 2022) - Sorum, Paul; Stein, Christopher; Wales, Danielle; Pratt, David
The process of developing and marketing new pharmaceuticals in the United States is driven by a need to maximize returns to shareholders. This results all too often in the production of new medications that are expensive and of marginal value to patients and society. In line with our heightened awareness of the importance of social justice and public health—and in light of our government's alliance with private companies in bringing us COVID-19 vaccines—we need to reconsider how new pharmaceuticals are developed and distributed. Accordingly, we propose the creation of a new agency of the Food and Drug Administration (FDA) that would direct the whole process. This agency would fund the research and development of high-value medications, closely monitor the clinical studies of these new drugs, and manage their distribution at prices that are value-based, fair, and equitable.